Pengaruh Profitabilitas, Likuiditas, dan Leverage Terhadap Opini Audit Going Concern Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Aysar Dimas Putra Pratama; Yusuf, Muhammad; Zakaria, Adam (LPPM Universitas Negeri Jakarta, 2025)
This study seeks to understand how factors like profitability, liquidity, and leverage affect the audit opinion regarding a company's ability to continue operating, with the size of the company acting as a variable that might influence this effect. This study employs a quantitative approach and uses secondary data from company financial statements. The target group for this study includes companies in the industrial sector that have been listed on the IDX from 2021 to 2023, totaling 66 companies. The method for selecting samples in this study is purposive sampling. The research employs Logistic Regression Analysis, and the data is analyzed using the Eviews 12 software. The findings reveal that profitability, liquidity, and leverage do not have an impact on the audit opinion concerning the company’s going concern status. Additionally, company size does not moderate the effects of profitability and leverage on the going concern audit opinion, while it does play a moderating role for liquidity regarding the going concern audit opinion. The findings suggest that the ratios utilized for evaluating a company's viability are not the sole tools for measurement.